Photophysical properties of a laser dye (LD-473) in different solvents. (June 2018) - Ibnaouf, K.H.; Alhathlool, R.; Ali, M.K.M.
Highlights: The spectral and ASE properties of LD-473 in two types of solvents were studied. The fluorescence of LD-473 in non-polar solvents showed only one peak at 437 nm. Under pulsed laser excitation LD-473 exhibited dual ASE peaks at 445 and 470 nm. The peak at 470 nm attributed to superexciplex. Abstract: In this paper, we investigated the spectroscopic properties the 1, 2, 3, 8-tetrahydrofuran, 2, 3, 8-(LD-473) dissolved in seven types of solvents with different concentrations. The absorption, emission, fluorescence and its quantum yield and Stokes shift of LD-473 were measured. The amplified spontaneous emission (ASE) spectra of LD-473 have been obtained using a transverse laser cavity configuration, where the LD-473 was pumped by laser pulses from the third harmonic of an Nd: YAG laser (355 nm). LD-473 in non-polar solvents exhibits dual ASEs around 445 and 470 nm, whereas the corresponding fluorescence spectrum shows only one peak around 437 nm. The peak at 470 nm is due to the combination of two excited molecules and the solvent between them.